PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MEMBENTUK IKLIM DAN BUDAYA ORGANISASI DI SDN 04 TEGALSARI KABUPATEN PEMALANG - Windriati; Hansen Lutfiartha; Noor Miyono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The principal's leadership plays a strategic role in determining the success of schools as educational organizations. This article examines how principals shape an organizational climate and culture conducive to achieving educational goals. This study employs a qualitative approach with a case study method in several schools known for their exemplary organizational culture. The findings reveal that effective principals can create a positive organizational climate through open communication, participatory decision-making, and recognition of achievements. Additionally, visionary and value-based leadership fosters a strong organizational culture characterized by collaboration, integrity, and innovation. Thus, the principal's role extends beyond that of an administrator to that of a change agent shaping the organization's character. These findings provide valuable insights for education practitioners in efforts to enhance school quality by strengthening organizational climate and culture.